Socialinių santykių bizantiškosios civilizacijos šalyse VII-XIV amžiuje tipologijos metmenys - Babinskas, Nerijus (Lietuvos istorijos studijos, 2005)
The main concepts which the author operates in his attempt to describe typologically a type of social relations in the area of Byzantine civilization in the Middle Ages are: an Asiatic mode of production, a slave mode of production, feudalism, and so-called semi-feudalism. According to E. Gudavičius, there were two ways of historical development of humankind: the main one (extensive) and the exceptional one (intensive). The absolute majority of civilizations developed towards the pattern of the main way. The first exception was Ancient Greece in the archaic period (VIII-VI century BC). The most important thing was that the idea of private property was born during that period. Rome also continued to develop in this direction, but at the end of antiquity, it reached a deadlock (during the barbarian invasions in the IV-V century AD). Nevertheless, the Roman ruins were "radioactive": Germanic tribes became acquainted with the idea of private property. Because of that, the allodial property of land and a holding of individual producers were born. So the exceptional way of production had reborn and had acquired a new quality. As a contrast, the productive cell of civilizations of the main way remained the community. There had been no private property. Such kinds of societies were ruled by a despot or a board of priests. These are the main features of the Asiatic mode of production. According to E. Gudavičius, the type of social structure characteristic of the Byzantine Empire and Russia could be described as semi-feudal. There were latifundia in Byzantium, but the owners of these latifundia exploited not the individual holdings of peasants but the whole communities. So the social structure of the Byzantine Empire remained transmixed between the slave and feudal modes of production. There was the same mixed model in Russia as in Byzantium. The ruling minority possessed private property, but peasants had no private property (it belonged to the community), though they had individual holdings. The ruler of Russia was even more autocratic than the Byzantine emperor. The countries of Southeastern Europe adopted the political as well as the sociocultural structure of the Byzantine Empire: the state was centralized, the church was subordinated to the state, the aristocracy did not rely on private property but on state distribution or redistribution, etc. The most advanced country of Southeastern Europe before the Ottoman conquering was Serbia: both Western and Byzantine cross-currents are visible in the mixed character of its political system, intermediate between the fief system and autocratic bureaucracy. According to P. Gunst, the lack of West European feudal property in land caused the absence of real feudal features in the area of Byzantine civilization. Because of that, the regions to the east of Central Europe developed on a different basis altogether. At the end, it should be said that there is not a properly developed conception yet about the type of social structure of the area of Byzantine civilization in the Middle Ages and also about certain subregions of the mentioned area (Byzantium, Russia, Southeastern Europe). It looks like the most successful term describing the social specifics of the medieval Byzantine area is semi-feudalism, but this conception is not properly developed either. So the conclusion is clear: there is still much to study if we want to describe the type of the Byzantine region's social structure more thoroughly.